Critical flicker frequency improves after alcohol detoxification and is associated with liver stiffness - Elshaarawy, Omar; Lan, Shuai; Müller, Johannes; Mueller, Sebastian (World journal of gastroenterology, 2025)
BACKGROUND - Critical flicker frequency (CFF) is a quantitative tool for assessing hepatic encephalopathy (HE), particularly minimal HE, which is associated with poor prognosis in liver cirrhosis. Alcohol-related liver disease (ALD) is a leading global cause of cirrhosis; however, the effects of alcohol on CFF and its relationship with liver stiffness (LS) remain underexplored. - - AIM - To study the impact of alcohol withdrawal on CFF and its correlation with LS in ALD patients. - - METHODS - A total of 108 patients were included: 93 heavy drinkers hospitalized for detoxification, 15 with non-ALD etiologies, and 20 healthy controls. CFF was measured using the Hepatonorm analyzer, and LS via transient elastography (FibroScan). Baseline and post-detoxification assessments were conducted in 57 ALD patients. - - RESULTS - The cohort had a mean age of 53.7 ± 13.8 years, with 74% male participants. CFF measurements were reliable, with 97.2% of patients showing an interquartile range < 20%. ALD patients exhibited significantly lower CFF compared to controls. Receiver operating characteristic analysis for overt HE (n = 12) yielded an area under the curve of 0.66 (95% confidence interval: 0.49-0.84, P = 0.0142), with an optimal cutoff of 36.5 Hz. CFF significantly improved post-detoxification. Patients with LS > 17 kPa had lower CFF, while those with intermediate LS showed no significant difference. - - CONCLUSION - CFF is influenced by HE severity and acute alcohol exposure, showing improvement after detoxification. Its weak correlation with fibrosis stage suggests that CFF serves as a sensitive neurocognitive marker in ALD.